2013
DOI: 10.1155/2013/134610
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Reduces Cocaine-Induced Seizures and Mortality in Mice

Abstract: The aims of this study were to characterize the protective profile of electroacupuncture (EA) on cocaine-induced seizures and mortality in mice. Mice were treated with EA (2 Hz, 50 Hz, and 100 Hz), or they underwent needle insertion without anesthesia at the Dazhui (GV14) and Baihui (GV20) acupoints before cocaine administration. EA at 50 Hz applied to GV14 and GV20 significantly reduced the seizure severity induced by a single dose of cocaine (75 mg/kg; i.p.). Furthermore, needle insertion into GV14 and GV20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…Similarly, the increase in the effect of PB when administered simultaneously with the electro-stimulation of SG-DM26 (KA-EA-PB) may be related to the increase in blood perfusion, as previously reported in cerebral ischemia, where an increase of blood perfusion in the brain decreased the penumbral area [58,59]. This demonstrates that EA facilitates intracerebral drug availability.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Similarly, the increase in the effect of PB when administered simultaneously with the electro-stimulation of SG-DM26 (KA-EA-PB) may be related to the increase in blood perfusion, as previously reported in cerebral ischemia, where an increase of blood perfusion in the brain decreased the penumbral area [58,59]. This demonstrates that EA facilitates intracerebral drug availability.…”
Section: Discussionsupporting
confidence: 56%
“…In contrast, the different effects between the KA-No-EA-PB and KA-EA-PB placebo groups, although not as effective in this model, can be attributed to the existing bioelectrical differences in acupuncture points. In these sites, a higher concentration of free nerve endings and neuroepithelial, neurovascular, and precapillary complexes have been reported around the acupuncture points, with a low electrical resistance, which gives them higher conductivity [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is an ancient therapy that gained worldwide acknowledgment in recent decades [ 1 ]. It involves inserting needles into acupoints followed by manual manipulation (manual acupuncture, MA) or electrostimulation (electroacupuncture, EA) to induce its therapeutic effect in epilepsy, [ 2 ] stroke, [ 3 ] and pain treatment [ 4 - 6 ]. To confirm its efficacy, clinical studies have shown its benefits, particularly in pain management [ 7 - 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…During EA stimulation period, animals were subjected to anesthesia with isoflurane inhalation with no pain response. Electrical stimulator (HC-0502, Home Care Technology, Co., Ltd., Tainan, Taiwan) provided 5 ms pulses at 100 Hz for 15 min following a previous study [9]. The current intensity was adjusted to evoke light muscle trembles (approximately 1.5–2 mV).…”
Section: Methodsmentioning
confidence: 99%